Development Of Community Welfare Based On Zakat Village Index Dimensions In Supporting Mustahik Economic Empowerment Institutions (LPEM) - Ghina Rohadatul Aisy; Akhris Fuadatis Solikha (Profesional Muda Cendekia Publishing, 2022)
The National Amil Zakat Agency or abbreviated as BAZNAS is a zakat management agency alleviating poverty and has a program, namely The Mustahik Economic Empowerment Institution (LPEM). The program provides assistance of productive zakat to the nedy village with the aim of improving the economy and living standard. The study aimed to analyze the community welfare development in Karangkemiri Village Pekuncen district Banyumas District on the Village Zakat Index (IDZ) basis which is going to be identified as eligible or not eligible for zakat fund assistance through (LPEM) and other form of productive zakat program which should be implemented. The methodology used is mixed method research, which is a combination of qualitative and quantitative methods to analyze research. Data were collected by means of interviews, questionnaires, observations and documentation obtained from the sources. The data analysis technique uses a calculation method called the multi stage weight index which is used to calculate the data resulting from the IDZ calculation, the presentation of the data presented in the form of tables and graphs, and drawing conclusions. The result indicated that the calculation of Village Zakat Index (IDZ) based on five dimension, namely: Economy, Health, Education, Social and Humanity, as well Dakwah. The result showed that Village Zakat Index (IDZ) in Karangkemiri Village Pekuncen district was 0.50. Karangkemiri Village was categorized as quite good if categorized into a score range, meaning that Karangkemiri village could be considered to be given the zakat by BAZNAS. If it was seen from economic dimension, Karangkemiri Village was prioritizedfor assistance.